ANALISIS TERHADAP APBD DINAS SOSIAL, TENAGA KERJA DAN TRANSMIGRASI KABUPATEN TEGAL PADA BELANJA PEGAWAI DAN BELANJA PUBLIK TAHUN ANGGARAN 2011 - Lina Setiawati; Budi Setyono; D Ghulam Manar (Journal of Politic and Government Studies, 2013)
This research was conducted to analysis about Local Revenue and Expenditure Budget (APBD) in Office of Social Walfare, Manpower and Transmigration of Tegal Regency in employee expenses and public expenses at 2011 Fiscal Year. The purpose of this research is to identify factors that determine allocation of budget on Office of Social Walfare, Manpower and Transmigration of Tegal Regency, the reason why employee expenses is bigger than public expenses anf also impact on public services, and obstacles that may be encountered when it committed to balance the expenditure between employee expenses and public expenses. This research using exploratory qualitative analysis by interviewed with the bureaucracy of Tegal Local Government about making process Local Revenue and Expenditure Budget (APBD) in Office of Social Walfare, Manpower and Transmigration of Tegal Regency, Wahana Karyatama NGO, and Radar Tegal. The secondary data obtained from the budget data regencies / cities in Indonesia at 2011 Fiscar Year from FITRA NGO. The results shows factors that determined allocation of budget in Office of Social Walfare, Manpower and Transmigration of Tegal Regency were based on tecnocratif, aspirative, and political approaches. When budget allocation for employee expenses is greater than public expenses, it will obstruct the public service. For instance the program of public service will be decrease every year because of budget allocation isn’t enough to cover it. The obstacles that will be encountered in balancing expenditure between employee expenses and public expenses is that high number of civil servant, cannot be easily reduced the employee expenses dan also increasing local revenue can not be implemented easily.